Output order and variability in free recall are linked to cognitive ability and hippocampal volume in elderly individuals - Bruno, Davide (Neuropsychologia, 2015)
Adapted from the work of Kahana and colleagues (e.g., Kahana, 1996), we present two measures of order of recall in neuropsychological free recall tests. These are the position on the study list of the first recalled item, and the degree of variability in the order in which items are reported at test (i.e., the temporal distance across the first four recalled items). We tested two hypotheses in separate experiments: 1) whether these measures predicted generalized cognitive ability, and 2) whether they predicted gray matter hippocampal volume. To test hypothesis 1, we conducted ordinal regression analyses on data from a group of 452 participants, aged 60 or above. Memory performance was measured with Rey's AVLT and generalized cognitive ability was measured with the MMSE test. To test hypothesis 2, we conducted a linear regression analysis on data from a sample of 79 cognitively intact individuals aged 60 or over. Memory was measured with the BSRT and hippocampal volume was extracted from MRI images. Results of Experiment 1 showed that the position of the first item recalled and the degree of output order variability correlated with MMSE scores only in the delayed test, but not in the immediate test. In Experiment 2, the degree of variability in the recall sequence of the delayed trial correlated (negatively) with hippocampal size. These findings confirm the importance of delayed primacy as a marker of cognitive ability, and are consistent with the idea that the hippocampus is involved in coding the temporal context of learned episodes.